Supra-renal aortic atheroma extent and composition predict acute kidney injury after transcatheter aortic valve replacement: A three-dimensional computed tomography study. (15th June 2023) - De Marzo, Vincenzo; Viglino, Umberto; Zecchino, Simone; Matos, Joao Gavina; Piredda, Elisa; Pigati, Maria; Vercellino, Matteo; Crimi, Gabriele; Balbi, Manrico; Seitun, Sara; Porto, Italo
Abstract: Objective: Acute kidney injury (AKI) may complicate transcatheter aortic valve replacement (TAVR) and could be linked to atheroembolization associated with catheter manipulation in the supra-renal (SR) aorta. We sought to determine the impact of SR aortic atheroma burden (SR-AAB) and composition, as well as of the aortic valve calcium score (AV-CS), measured at pre-operative multislice computed tomography (PO-MSCT), on AKI-TAVR. Methods: All TAVR-patients 3 January-2018 to December-2020 were included. A three-dimensional analysis of PO-MSCT was performed, calculating percentage SR-AAB (%SR-AAB) as [(absolute SR-AAB volume)*100/vessel volume]. Types of plaque were defined according to Hounsfield unit (HU) intensity ranges. Calcified plaque was subcategorized into 3 strata: low- (351–700 HU), mid- (701–1000 HU), and high‑calcium (>1000 HU, termed 1 K-plaque). Results: The study population included 222 patients [mean age 83.3 ± 5.7 years, 95 (42.8%) males], AKI-TAVR occurred in 67/222 (30.2%). Absolute SR-AAB (41.3 ± 16.4 cm 3 vs. 32.5 ± 10.7 cm 3, p  < 0.001) and %SR-AAB (17.6 ± 5.1% vs. 13.9 ± 4.3%, p < 0.001) were significantly higher in patients developing AKI-TAVR. Patients who developed AKI-TAVR had higher mid‑calcium (6.9 ± 3.8% vs. 4.2 ± 3.5%, p  < 0.001) and 1 K-plaque (5.4 ± 3.7% vs. 2.4 ± 2.4%, p < 0.001) with no difference in AV-CS ( p  = 0.691). Adjusted multivariable logistic regression analysis showed that %SR-AAB [OR (x%increase): 1.12, 95%CI: 1.04–1.22, p  = 0.006] and %SR-calcified plaque [OR (x%increase): 5.60, 95%CI: 2.50–13.36, p  < 0.001] were associated with AKI-TAVR. Finally, 3-knots spline analyses identified %SR-AAB >15.0% and %SR-calcified plaque >7.0% as optimal thresholds to predict an increased risk of AKI-TAVR. Conclusions: Suprarenal aortic atheroma, when highly calcified, is associated with AKI-TAVR. Perioperative-MSCT assessment of aortic atherosclerosis may help in identification of patients at high-risk for AKI-TAVR, who could benefit from higher peri-operative surveillance. Graphical abstract: Unlabelled Image Highlights: Among 222 TAVR patients, 67 (30.2%) showed post-TAVR acute kidney injury (AKI). 3-dimensional multislice computed tomography could be useful in pre TAVR evaluation. AKI patients had higher supra-renal aortic atheroma burden (SR-AAB) and calcified plaque. The risk of AKI increases when %SR-AAB is >15.0% and %SR-calcified plaque is >7.0%.